Penerapan Psikoedukasi Nomophobia Terhadap Insight Siswa SDN Bojong 02 Kemang Bogor Dalam Penggunaan Gadget - Tarisafitri, Nahla; Hilaliyah, Maimunah; Wahyudin, Aris; Azhari, Azhari; Ali, Ircham (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Gadgets in various forms and functions have become a crucial part of life everyday Indonesian society. Over time, gadgets have become an integral part inseparable from their lives. The kids from before may be more familiar traditional games in the open air now tend to be more time consuming them with gadgets. However, behind the comfort and practicality offered by This technology has increasingly disturbing negative impacts, one of which is gadget addiction. Apart from that, gadgets also have a psychological impact, such as An anxiety disorder known as no mobile phone phobia or nomophobia. This activity took the form of psychoeducation which was carried out at SDN Bojong 02 Kemang Bogor. The method used is interactive lectures and discussions and is processed descriptively, with one group pretest and posttest as well as FGD. This psychoeducation aims to provide insight to students regarding the impact of excessive gadget use. The results of this research show that psychoeducation has influence and is capable increase insight into gadgets.